EFEKTIVITAS KEBIJAKAN MONETER DAN FISKAL DALAM MENJAGA STABILITAS EKONOMI DI ERA PASCA PANDEMI - Dianda Hashifah; Yunita Dwi Rahmawati; Muhammad Arfan Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This research aims to analyze the effectiveness of monetary and fiscal policies in maintaining Indonesia’s economic stability in the post-pandemic era. The COVID-19 pandemic caused significant disruptions to economic growth, price stability, and the national financial system, requiring appropriate and well-coordinated macroeconomic policy responses. Fiscal policy, implemented through increased government spending and economic stimulus, is expected to support economic recovery, while monetary policy plays a crucial role in controlling inflation and maintaining financial liquidity. This research employs a qualitative descriptive approach using a literature review method by examining relevant scientific journals, policy reports, and official publications published since 2020. The findings indicate that strong coordination between monetary and fiscal policies is essential in maintaining economic stability and accelerating post-pandemic recovery. However, policy effectiveness is highly influenced by global economic conditions, institutional coordination, and the timing of policy implementation. Therefore, strengthening policy coordination and conducting continuous evaluations are necessary to ensure that monetary and fiscal policies operate effectively and sustainably in addressing future economic challenges.